1992
DOI: 10.2307/2388476
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Selection and Sexual Dimorphism in the Harlequin Beetle Acrocinus longimanus

Abstract: To investigate the causes of striking sexual dimorphism in the harlequin beetle (Acrocinus longimanus), we carried out a study of the behavior and morphology of two widely separated populations (in French Guiana and Panama). Males of this species possess greatly elongated forelegs which exhibit strong positive dometry with body size (elytra length). Males use their forelegs in fights with other males and in guarding females and oviposition sites. Field data on fighting and mating success suggest that sexual se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 28 publications
(8 reference statements)
1
38
0
4
Order By: Relevance
“…Sexual selection is expected to continuously favor large weapon sizes (Parker 1979(Parker , 1983West Eberhard 1983;Andersson 1994), and horned beetles fit this pattern: in every species tested thus far, males with the longest horns won disproportionate access to females (Eberhard 1982;Goldsmith 1987;Siva-Jothy 1987;Zeh and Zeh 1992;Rasmussen 1994;Emlen 1997;Moczek and Emlen 2000). Yet, our phylogeny suggests that complete loss of all horns has occurred at least three times (branches leading to O. pennsylvannicus; to O. cochisus, O. coscineus, and O. knulli; and to O. muticus).…”
Section: Loss Of Hornsmentioning
confidence: 99%
“…Sexual selection is expected to continuously favor large weapon sizes (Parker 1979(Parker , 1983West Eberhard 1983;Andersson 1994), and horned beetles fit this pattern: in every species tested thus far, males with the longest horns won disproportionate access to females (Eberhard 1982;Goldsmith 1987;Siva-Jothy 1987;Zeh and Zeh 1992;Rasmussen 1994;Emlen 1997;Moczek and Emlen 2000). Yet, our phylogeny suggests that complete loss of all horns has occurred at least three times (branches leading to O. pennsylvannicus; to O. cochisus, O. coscineus, and O. knulli; and to O. muticus).…”
Section: Loss Of Hornsmentioning
confidence: 99%
“…This phoretic association has been reported more than a century ago (e.g. Ellingsen 1905), where the Harlequin beetle is the obligate dispersal agent of C. scorpioides (Zeh, Zeh & Tavakilian 1992;Zeh & Zeh 1994a, 1994b. Despite the wide distribution of this beetle species across the Neotropics, little is known about the distribution of this phenomenon (e.g.…”
Section: Introductionmentioning
confidence: 60%
“…Although the populations from French Guiana and Panama experience markedly different climates and microhabitats (Zeh et a!., 1992), we have found that they share a complex set of behaviours associated with dispersal and male competition. The pseudoscorpion disperses from old to newly dead or dying trees under the elytra of the giant harlequin beetle, Acrocinus longimanus (Zeh & Zeh, 1992a,b, Zeh eta!., 1992.…”
Section: Comparison Of Band-sharing Coefficientsmentioning
confidence: 73%